The Effect of the Story Map Method in Narrative Text to Improve Students' Reading Skills - Irmala Sukendra; Delvia Chahyadin; Ambuy Sabur (Foremost Journal, 2025)
Investigation on instructional strategies provides valuable insights that contributes to students? better academic outcomes. This study aims to determine the significant effect of using the story map method on improving the reading skills of eleventh-grade science students at Madrasah Aliyah Attaqwa Tangerang. The research specifically focuses on their comprehension of narrative text learning material during the 2023/2024 academic year. This study employed a Quasi-Experimental Design. The research population consisted of all eleventh-grade science (XI IPA) students at Madrasah Aliyah Attaqwa Tangerang for the 2023/2024 academic year. The sample size was 30 students. Data were collected through pre-test and post-test instruments to measure student reading skills before and after the intervention. The collected data were tested for assumptions and found to be both normally distributed and homogeneous. Subsequently, hypothesis testing was conducted using a paired sample t-test. The results of the hypothesis test led to the rejection of the null hypothesis (Ho) and the acceptance of the alternative hypothesis (Ha). This indicates a statistically significant positive effect from using the story map method. Therefore, it is concluded that the story map method effectively improves the reading skills of eleventh-grade science students at Madrasah Aliyah Attaqwa Tangerang in narrative text comprehension.